2016
DOI: 10.1002/2016gl070153
|View full text |Cite
|
Sign up to set email alerts
|

Radiative forcing from anthropogenic sulfur and organic emissions reaching the stratosphere

Abstract: Stratospheric aerosols cool the Earth by scattering sunlight. Although sulfuric acid dominates the stratospheric aerosol, this study finds that organic material in the lowermost stratosphere contributes 30–40% of the nonvolcanic stratospheric aerosol optical depth (sAOD). Simulations indicate that nonvolcanic sAOD has increased 77% since 1850. Stratospheric aerosol accounts for 21% of the total direct aerosol radiative forcing (which is negative) and 12% of the total aerosol optical depth (AOD) increase from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 41 publications
(53 reference statements)
5
39
0
Order By: Relevance
“…Furthermore, the relevance of UT aerosol production may not be limited to the troposphere, because the UT and the TTL are also important reservoirs for the transport of particles into the lower stratosphere (Fueglistaler et al, 2009;Borrmann et al, 2010;Randel and Jensen, 2013). Organic aerosols in the lower stratosphere have been shown to have significant radiative effects (Yu et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relevance of UT aerosol production may not be limited to the troposphere, because the UT and the TTL are also important reservoirs for the transport of particles into the lower stratosphere (Fueglistaler et al, 2009;Borrmann et al, 2010;Randel and Jensen, 2013). Organic aerosols in the lower stratosphere have been shown to have significant radiative effects (Yu et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The transport of aerosols from the Asian boundary layer to the UTLS by the monsoon convection is known to form and maintain the Asian Tropopause Aerosols Layer (ATAL) (SPARC-ASAP, 2006;Fadnavis et al, 2013;Vernier et al, 2015Vernier et al, , 2018Yu et al, 2017). In the future, the aerosol burden in the UTLS may increase due to rising trends in aerosol emission.…”
Section: Introductionmentioning
confidence: 99%
“…The major sources of aerosols in the ATAL are found in India and China, with Indian emissions dominating the composition of the ATAL (Lau et al, 2018). Climate model simulations show that the Asian monsoon region (15-45 • N, 30-120 • E) is 3 times more efficient (per unit area and time) in enhancing aerosol in the Northern Hemisphere stratosphere than annually averaged tropical (15 • N-15 • S) upwelling (Yu et al, 2017). Although the chemical composition of the particles constituting the ATAL is not well understood, satellite observations (e.g., Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation, CALIPSO; Stratospheric Aerosol and Gas Experiment, SAGE-II; balloon sonde and aircraft measurements; Civil Aircraft for the Regular Investigation of the atmosphere Based on an Instrumented Container, CARIBIC) suggest that ATAL particles may contain large amounts of sulfate, as well as black carbon, organic, nitrates (including ammonium nitrate) and dust (Vernier et al, 2015(Vernier et al, , 2018Yu et al, 2016;Höpfner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Filter measurements [ Junge et al , ], volatility measurements [ Rosen , ; Borrmann et al , ], and mass spectrometer measurements [ Arnold et al , ; Murphy et al , ] all point to SA being dominated by sulfuric acid (H 2 SO 4 )‐water mixtures, although recent work has shown that in the upper troposphere and lower stratosphere (UT/LS) organic material may sometimes be a significant fraction of the mass [ Brühl et al , ; Murphy et al , ; Yu et al , ]. Crutzen [] originally proposed that oxidation of carbonyl sulfide (OCS) to form H 2 SO 4 might play a dominant role as a source of SAs because of its ubiquitous tropospheric mixing ratio of ~500 parts per trillion by volume (pptv) and its efficient photolytic destruction in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%